Comment devient-on homo ou hétéro? - Clerget, Stéphane (JC Lattès, 2006)
Le pédopsychiatre présente les découvertes récentes de la psychanalyse, la neurobiologie, la génétique, l'histoire, la sociologie, etc., à propos de la construction de l'identité sexuelle et de la part d'inné et d'acquis dans la définition des préférences sexuelles.
Section: 428 pages ; 23 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; europe; france; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lesbianisme; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

A bakhtinian perspective on feminist lesbian crime writing - Posman, Sarah (CLCWeb: Comparative Literature and Culture, 2006)
In her paper, "A Bakhtinian Perspective on Feminist Lesbian Crime Writing," Sarah Posman discusses how the Bakhtinian concepts "ethos" and "chronotope" add to the discussion of feminist lesbian crime writing. She sets out from a Bakhtinian typology of action stories and situates recent crime writing as a curious mixture of mission stories and transformation stories. Focusing on the innovative potential of feminist lesbian crime writing, Posman explores how such stories tackle the iconically masculine and heterosexual conventions of the detective story and manage to balance tradition and subversion successfully. Posman infuses her analysis with issues central to feminism and queer theory and considers how a feminist lesbian detective hero can "change the world," that is, how such an "other" ethos impinges on crime writing's conventional chronotopical constellation. The hero and world under discussion are those of the popular Kate Delafield series by Katherine V. Forrest.
Keywords: approches et analyses; arts; discipline; lesbianisme; personnes lesbiennes; queer; ressource en ligne; études littéraires